2020
DOI: 10.1093/gerona/glaa243
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors for Mortality in Very Old Patients Hospitalized With COVID-19 in Spain

Abstract: Background Advanced age is a well-known risk factor for poor prognosis in COVID-19. However, few studies have specifically focused on very old inpatients with COVID-19. This study aims to describe the clinical characteristics of very old inpatients with COVID-19 and identify risk factors for in-hospital mortality at admission. Methods We conducted a nationwide, multicenter, retrospective, observational study in patients ≥80 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
102
5
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 41 publications
12
102
5
4
Order By: Relevance
“…In a younger cohort, Mostaza et al (20), in people older than 75 years, did nd a better prognosis in patients who previously took reninangiotensin-aldosterone system antagonists. Regarding previous chronic diseases, our results are similar to the study by Ramos-Rincon et al (9); however, Covino et al (10) reported severe dementia as an independent risk factor for death, although age, since it was not apparently included in their multivariate analysis, cannot be rule out as a confounding factor.…”
Section: Predictors Of Severe Disease and Mortalitysupporting
confidence: 90%
See 2 more Smart Citations
“…In a younger cohort, Mostaza et al (20), in people older than 75 years, did nd a better prognosis in patients who previously took reninangiotensin-aldosterone system antagonists. Regarding previous chronic diseases, our results are similar to the study by Ramos-Rincon et al (9); however, Covino et al (10) reported severe dementia as an independent risk factor for death, although age, since it was not apparently included in their multivariate analysis, cannot be rule out as a confounding factor.…”
Section: Predictors Of Severe Disease and Mortalitysupporting
confidence: 90%
“…The trials by Gutiérrez-Rodríguez et al (11) and Covino et al (10) did not nd that age or sex were predictors of mortality either. However, Ramos-Rincon et al (9) reported age and male sex as predictors of mortality from a multicentre cohort of 2772 very old hospitalized patients so we cannot rule out a lack of statistical power of our sample in these results.…”
Section: Predictors Of Severe Disease and Mortalitymentioning
confidence: 76%
See 1 more Smart Citation
“…Aging is one of the most signi cant factors associated with a poor prognosis in coronavirus disease-2019 (COVID-19) [1][2][3][4]. In addition, diabetes is a common comorbidity among patients with severe COVID-19 [5,6] and while it does not increase susceptibility to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, it has also been correlated with a more severe course of COVID-19 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies speci cally reporting on clinical presentation and prognostic factors in the oldestold population [9][10][11]. The main reported symptoms of clinical presentation have included fever, dyspnoea, cough, and deterioration of functional status; and factors associated with higher mortality included age, male sex, severe functional dependence, cognitive decline, renal function, and in ammatory markers.…”
Section: Introductionmentioning
confidence: 99%